نطاق التحكيم في المسائل المتعلقة بالأحوال الشخصية في الفقه الإسلامي وقانون التحكيم الفلسطيني رقم (3) لسنة 2000 - صعابنة, محمد; سهيل, الأحمد (Revue jurisprudence, 2018)
تناولت هذه الدراسة نطاق التحكيم في المسائل المتعلقة بالأحوال الشخصية في الفقه الإسلامي وقانون التحكيم الفلسطيني، هادفة إلى التعرف على ماهية التحكيم في هذه المسائل وطبيعته ونطاق تطبيقه في مسائل الأحوال الشخصية. وقد تم الوقوف على حقيقة التحكيم، ومشروعيته، والمبررات العملية لوجوده، والتعريف باتفاق التحكيم وشروط صحته، وحدود النزاعات المعروضة على هيئة التحكيم في مسائل الأحوال الشخصية، ومدى قابلية هذه النزاعات للتحكيم. وعالج البحث ضوابط التحكيم في مسائل الأحوال الشخصية، وبين كذلك الأمور التي يجوز فيها التحكيم في الأحوال الشخصية والأمور التي لا يجوز فيها هذا الأمر وفق الفقه الإسلامي وقانون التحكيم الفلسطيني. حيث ظهر أن التحكيم من المسائل المهمة في التشريع الفقهي والقضائي، وبأن الهدف منه أن يعرف أطراف النزاع حقوقهم من النواحي الشرعية والقانونية، وأما صور التحكيم وحالاته في المسائل المتعلقة بالأحوال الشخصية فقد تبين أنها متعددة من حيث المشروعية وعدمها وفق تفصيلات وردت في هذا البحث. الكلمات المفتاحية: التحكيم الشرعي، نطاق التحكيم، الأحوال الشخصية.   The scope of Arbitration in the Affairs Related to Personal Status in the Islamic Jurisprudence and the Palestinian Arbitration Law No. 3 of 2000 Dr. Muhammed Sa'abnah & Dr. Suhail Al-Ahmad (Department of Law, Palestine Ahliya University College, Bethlehem) Abstract: This study deals with the scope of arbitration in matters related to personal status in Islamic jurisprudence and the Palestinian Arbitration Law. It aims at identifying the nature of arbitration in these matters and the nature and scope of its application in matters of personal status. The nature of the arbitration, its legitimacy and the practical justifications for its existence, have been all referred to. Besides, the definition of the arbitration agreement and the conditions of its validity, the limits of disputes before the arbitral tribunal on personal status matters, and the arbitrability of such disputes have been explained. The research deals with the arbitration rules in matters of personal status, as well as the matters in which arbitration may be held in personal cases and the issues which are not permissible according to the Islamic jurisprudence and the Palestinian arbitration law. It has been found that arbitration is an important issue in jurisprudence and jurisprudence legislation, and that its aim is for the parties to the dispute to know their rights in terms of legality and legislation. The forms of arbitration and its cases in the issues related to personal status have been found to be multiple in terms of legality and lack of legality according to some details listed in this paper. Keywords:   Jurisdiction, Scope of arbitration, Personal status.